Modern Methods of Treatment of Flaming Nevus - U.A.Tashkenbayeva; M.R. Mukhamedova (Genius Journals, 2023)
Histological and immunohistochemical research methods make it possible to reliably judge the degree of dysplastic changes in the epidermis in AK and its invasive potential. However, in most cases, the sampling of biopsy material causes certain difficulties, as it can leave cosmetic defects. Considering that the most common localization of AK is the skin of the face, it seems relevant to use more widely non-invasive research methods in the diagnosis and determination of the nature of the growth
Keywords: Medicine; Methodology; dermatovenereology